Annaeana tragica : notes on the text of Seneca's tragedies - Fitch, John G. (Mnemosyne, Supplements, 2004)
This volume is a companion to the author's new Loeb edition of Seneca's tragedies (vol. 1, 2002; volume 2, 2004). It offers reasons for his editorial choices, and explains his interpretations of the text as reflected in his translation. Hercules Oetanus and Octavia , now generally regarded as imitations of Senecan drama, are both included. The volume is intended to be read alongside Otto Zwierlein's Kritische Kommentar , published in 1986. In the intervening years there has been much new work pertaining to Seneca's text, including full-scale editions with commentary on individual plays, such as Keulen's Troades , Töchterle's Oedipus and Ferri's Octavia . Annaeana Tragica seeks to supplement and advance Zwierlein's work in the light of this new material. An appendix reviews the scholarly controversy concerning the anapaestic odes of these plays, and offers fresh evidence relevant to the issue.